مشروع سد أليسو اليسو التركي وأثره علئ حقوق العراق المانية في ظل قانون الدواي والشريعة الأسلامية - Ahmed Basim Hattab Altumma
The present study tackles the attitudes of both the international law and Islamic Shari’s (law) towards Turkey’s construction of Ilisu Dam at the Tigris, and consequently the serious damages inflicted on Iraq. It shows how such a construction contradicts the U.N. Agreement of 1997 which organized the legal application of the international riverbeds and imposed upon the U.N. member states to abide by it. The Tigris, according to the definition of the international river, based on the agreements concluded between Iraq and Turkey, is, in fact, an international river. Any state sharing this river, as such, has no right to encroach upon the water rights of other states and is completely subject to the international law in force (1997). This refutes Turkey’s allegations that the Tigris is a Turkish national trans-border river, and so it has a full right to act freely towards its water, with no consideration for the interests of other littoral countries. This includes setting up dams and other giant utilities of which Ilisu Dam is the most outstanding and biggest. Turkey is, therefore, bound by international law to refrain from undertaking any unilateral procedures that could deactivate the natural system of the river. This, however, would damage Iraq’s own water right. Besides that, the Islamic Shari’a has a key role to play in this respect. Turkey, an Islamic state, has to be influenced by Islam’s magnanimous message in tackling shared waters with Iraq. As such, Turkey should study and analyze the international laws in force, together with the Islamic precepts related to water. The two neighboring countries, Iraq and Turkey, should resolve any disputes in harmony with the Holy Qur’an and the noble Sunna of Prophet Mohammad (PBUH). Taking a tangible step, Turkey has to build up and operate Ilisu Dam in agreement with Iraq, taking into account Iraq’s legal right in Tigris water. On its part, Iraq, being situated down the river, has to compensate for the shortage of water by adopting modern techniques in handling water, for drinking purposes or otherwise.